Improving Technical and Bureaucratic Writing; Science Magazines: The Second Wave Rolls In; Extraordinary Science Essays of the Past Half Century; Update: Technical Communication at Rensselaer - Dot Sparer (Journal of Applied Communications, 1982)
Reviews of "Improving Technical and Bureaucratic Writing," by Mohan R. Limaye; "Science Magazines: The Second Wave Rolls In," in Science; "Extraordinary Science Essays of the Past Half Century," by Richard Conniff; "Update: Technical Communication at Rensselaer," in Journal of Technical Writing and Communication.